1999
DOI: 10.1111/j.1600-0536.1999.tb06086.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy to corticosteroids in asthma/rhinitis patients

Abstract: Patients with asthma and/or rhinitis, when using inhalers or nasal sprays containing corticosteroids, may experience mucosal symptoms, such as congestion of the nose, itching, nose bleeding and worsening of rhinitis, but also eczema of the face sometimes spreading to flexures, and sometimes the corticosteroid simply does not help. Few patients with such symptoms have been found to be allergic to their inhaled corticosteroids (1), and no report on whether contact allergy to corticosteroids could explain treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…Occasionally, contact allergy to corticosteroids may express itself as acute eczema, acute local edema (13, 14), immediate-type reaction (15), or an id-like spread (including erythema multiforme-like symptoms) (16,17) elsewhere on the body. Moreover, previously sensitized patients can present with systemic contact dermatitis, exanthema, purpura, and urticaria after the administration of systemic (orally or injected) corticosteroid preparations (18±22, Goossens, unpublished results), or, although this is infrequent relative to the very frequent use, allergic reactions can be observed to corticosteroids administered by inhalation preparations in the treatment of rhinitis or bronchial asthma (23,24).…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…Occasionally, contact allergy to corticosteroids may express itself as acute eczema, acute local edema (13, 14), immediate-type reaction (15), or an id-like spread (including erythema multiforme-like symptoms) (16,17) elsewhere on the body. Moreover, previously sensitized patients can present with systemic contact dermatitis, exanthema, purpura, and urticaria after the administration of systemic (orally or injected) corticosteroid preparations (18±22, Goossens, unpublished results), or, although this is infrequent relative to the very frequent use, allergic reactions can be observed to corticosteroids administered by inhalation preparations in the treatment of rhinitis or bronchial asthma (23,24).…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…Postulated unresponsiveness or symptom deterioration in response to the corticosteroid treatment may also be symptoms of corticosteroid allergy. 4,5 Concentrations and vehicles for corticosteroid patchtesting have not been standardised yet, and the existing commercial T.R.U.E. test includes three corticosteroids, namely budesonide, tixocortol-21-pivalate and hydrocortisone-17-butyrate.…”
Section: Introductionmentioning
confidence: 99%
“…Nasal congestion (29) Erythema and/or oedema of the buccal mucosa (46,49) Generalized eruption (35) Generalized erythematous, macular, maculopapular, papulo-vesicular, pustular, purpuric or eczematous eruptions (6) Chronic eczema, irritant dermatitis on the hands and/or feet (35) Pruritus, dry or burning sensation…”
Section: Local Irritationmentioning
confidence: 99%
“…pruritus, vertigo, shaking, malaise, angina, bronchospasm, nausea, vomiting, abdominal pain, melaena) (64,67) Cutaneous lesions at some distance from the application zone (37,38) Marked reduction of FEV1 (51-53) Shock and cardio-respiratory failure (68) Photo contact allergy (42) Bronchospasm, bronchoconstriction (52, 53) Generalized maculo-erythematous or eczematous eruption (54) Diffuse pruritus (29) Urticaria, angioedema (29,55) Allergic reaction in subjects not themselves treated by inhalers, but responsible for or living with patients who use inhalers regularly (56) Allergic hypersensitivity to topical and systemic corticosteroids multi-centre European study has shown that more than 50% of patients with an allergy to tixocortol pivalate were not detected with this mix (75), presumably due to masking by the anti-inflammatory effect of the other constituents. This method cannot therefore replace testing with individual markers.…”
Section: Angioedemamentioning
confidence: 99%
See 1 more Smart Citation